Long Non-Coding RNAs in the Control of Gametogenesis: Lessons from Fission Yeast - Vedrana Andric; Mathieu Rougemaille (Non-Coding RNA, 2021)
Long non-coding RNAs (lncRNAs) contribute to cell fate decisions by modulating genome expression and stability. In the fission yeast Schizosaccharomyces pombe, the transition from mitosis to meiosis results in a marked remodeling of gene expression profiles, which ultimately ensures gamete production and inheritance of genetic information to the offspring. This key developmental process involves a set of dedicated lncRNAs that shape cell cycle-dependent transcriptomes through a variety of mechanisms, including epigenetic modifications and the modulation of transcription, post-transcriptional and post-translational regulations, and that contribute to meiosis-specific chromosomal events. In this review, we summarize the biology of these lncRNAs, from their identification to mechanism of action, and discuss their regulatory role in the control of gametogenesis.